(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: During General Military Training, female military recruits undergo vigorous physical stress. A significant proportion of individuals experience the medical condition known as anaemia which further deteriorates due to training activities. Objective: To determine the effectiveness of selected dietary supplements in improving the haemoglobin status of female military recruits in the Army Medical Corps Centre and School. Methods: The study was experimental, following one sample pre-test and post-test design. It was conducted among 48 female military recruits undergoing General Military Training at the Army Medical Corps Centre and School. Selected dietary supplements were administered among the participants for six and half months in addition to the standard menu. Their haemoglobin status was determined by three consecutive laboratory tests. Results: In the initial test, 66.7% of female recruits were found anaemic and the mean haemoglobin level was 11.477 ±1.099. After administering selected dietary supplements, 33.3% and 27.1% were found anaemic after three months and six and half months and the mean haemoglobin levels were 12.215±0.917 and 12.538±0.937 respectively. Statistically significant differences were found among the mean haemoglobin level of the three consecutive tests (P<0.05). Conclusion: Considering the health condition of newly enrolled female military recruits, the daily menu can be revised by adding selected diets and dietary supplements during General Military Training. Periodic screening for haemoglobin status may be recommended. JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 3-7